2020
DOI: 10.1177/1098612x20972066
|View full text |Cite
|
Sign up to set email alerts
|

Lomustine, methotrexate and cytarabine chemotherapy as a rescue treatment for feline lymphoma

Abstract: Objectives The aim of this study was to assess the efficacy and tolerability of lomustine, methotrexate and cytarabine chemotherapy as rescue treatment for feline lymphoma. Methods The medical records of 13 cats treated with lomustine, methotrexate and cytarabine for relapsed high-grade feline lymphoma, at a single institution between 2013 and 2018, were examined. All anatomical types were included. Data were analysed using descriptive statistics. Results Nine cats received all three drugs and four cats receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In the present case, nephrectomy was performed and adjuvant chemotherapy with CCNU started at the standard dose of 50 mg/m 2 , as previously reported 32 . The time interval between lomustine administrations in cats is reported to range between 3 and 6 weeks, depending on the study 10,33–36 . Albeit in a phase I trial the authors suggested to use lomustine in cats every 6 weeks due to a late onset of neutropenia (up to 28 days), a subsequent study showed that the drug could be safely administered every 21 days, considering high‐grade haematological AEs were infrequently reported 32,37 …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the present case, nephrectomy was performed and adjuvant chemotherapy with CCNU started at the standard dose of 50 mg/m 2 , as previously reported 32 . The time interval between lomustine administrations in cats is reported to range between 3 and 6 weeks, depending on the study 10,33–36 . Albeit in a phase I trial the authors suggested to use lomustine in cats every 6 weeks due to a late onset of neutropenia (up to 28 days), a subsequent study showed that the drug could be safely administered every 21 days, considering high‐grade haematological AEs were infrequently reported 32,37 …”
Section: Discussionmentioning
confidence: 53%
“…32 The time interval between lomustine administrations in cats is reported to range between 3 and 6 weeks, depending on the study. 10,[33][34][35][36] Albeit in a phase I trial the authors suggested to use lomustine in cats every 6 weeks due to a late onset of neutropenia (up to 28 days), a subsequent study showed that the drug could be safely administered every 21 days, considering high-grade haematological AEs were infrequently reported. 32,37 In our case, treatment was well tolerated even though it was administered every 3 weeks, with no development of haematological AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of several chemotherapeutic agents such as lomustine, mechlorethamine, methotrexate, cytarabine, actinomycin D and melphalan has been reported for relapsed feline lymphoma in various sites (including the nasal cavity), response rates were typically poor with median progression-free survival ranging from 14 to 61 days. [13][14][15][16] Chlorambucil is most commonly used to treat low-grade gastrointestinal lymphoma in cats and is well tolerated. [17][18][19][20] Adverse effects associated with chlorambucil are generally mild relative to those of the aforementioned rescue protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of several chemotherapeutic agents such as lomustine, mechlorethamine, methotrexate, cytarabine, actinomycin D and melphalan has been reported for relapsed feline lymphoma in various sites (including the nasal cavity), response rates were typically poor with median progression-free survival ranging from 14 to 61 days. 1316…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma is one of the most common types of cancer in cats, and chemotherapy is often the treatment of choice for this disease [1][2][3][4][5][6]. The expected survival rate in animals treated with multidrug chemotherapy protocols is 6-9 months, and the remission rate is approximately 65-75% [7].…”
Section: Introductionmentioning
confidence: 99%